Determinants of foreign direct investments outflow from a developing country: the case of Turkey - Onder, Gokhan; Karal, Zeynep (Business, Management and Economics Engineering, 2013)
Foreign direct investments (FDI) outflows of Turkey have remarkably been raising over the last decade. This rapid increase brings about the need for questioning the determinants of FDI outflows. The aim of this paper is to estimate the factors affecting outflow FDI from Turkey from 2002 to 2011 by using Prais-Winsten regression analysis. According to estimation results, population, infrastructure, percapita gross domestic product of the host country, and home country exports to the host country are the factors having positive effects on outflow FDI. We found, on the other hand, that the annual inflation rate of the host country, its tax rate collected from commercial profit, and its distance from Turkey have a negative relation with investment outflows. Moreover our results show that while investment outflows to developed countries are in the form of horizontal investments, investment outflows to developing countries are in the form of vertical investments.